Le temps de la justice aux premiers siècles de l’Islam - Mathieu Tillier (Revue des Mondes Musulmans et de la Méditerranée)
The courts of the first centuries of Islam established schedules organizing the work of the court. The judges’ regular hearings allow at least partial reconstruction of their daily and weekly schedules. Scheduled audiences and hearings were also an imposition on litigants, who were required to interrupt their daily routines to appear in court or submit themselves to proceedings that could sometimes be very lengthy. Finally, time is presented as a legal instrument, which may influence the course of the trial and be subject to judgments. This article explores some aspects of these issues in the eastern provinces under the Umayyad and Abbasid dynasties.